Irisin immunostaining characteristics of breast and ovarian cancer cells - Kuloglu, T.; Celik, O.; Aydin, S.; Ozercan, I. Hanifi; Acet, M.; Aydin, Y.; Kocaman, N. (C M B Assoc, 2016)
To determine expression pattern of irisin in tissues obtained from human ovarian cancer, breast cancer, and cervix cancer. Tissue samples obtained from subjects with breast cancer, ovarian cancer cervix cancer, simple endometrial hyperplasia, complex atypical endometrial hyperplasia. At least five sections from each subject were immunohistochemically stained with irisin antibody, and H-score method was used to evaluate irisin intensity. Tissues obtained from healthy breast tissues, proliferative phase endometrium adenomyosis and benign ovarian tumors were accepted as control. Irisin activity was not detected in control breast tissues significantly increased irisin staining was detected in invasive lobular, intraductal papillary, invasive ductal, invasive papillary, and mucinous carcinomas compared to control tissues. Also, significantly increased irisin immunoreactivity was detected in both ovarian endometriosis and mucinous carcinomas compared to benign tumors. However irisin staining was not observed at the papillary carcinoma of the ovary while sections obtained from simple and complex atypical endometrial hyperplasia, and cervix carcinoma demonstrated irisin immunoreactivity. Increased irisin immunoreactivity in tissues obtained from breast, ovary, cervix carcinomas, and endometrial hyperplasia suggest critical role of this peptide during carcinogenesis.
Keywords: Irisin; Breast cancer; Ovarian cancer; Cervix cancer; Endometrial hyperplasia